Optical properties of metamorphic type-I InAs1−xSbx/Aly In1−y As quantum wells grown on GaAs for the mid-infrared spectral range. (30th August 2019) - Repiso, Eva; Broderick, Christopher A; de la Mata, Maria; Arkani, Reza; Lu, Qi; Marshall, Andrew R J; Molina, Sergio I; O'Reilly, Eoin P; Carrington, Peter J; Krier, Anthony
Abstract: We analyse the optical properties of InAs1− x Sb x /Al y   In1− y   As quantum wells (QWs) grown by molecular beam epitaxy on relaxed Al y   In1− y   As metamorphic buffer layers (MBLs) using GaAs substrates. The use of Al y   In1− y   As MBLs allows for the growth of QWs having large type-I band offsets, and emission wavelengths  >3 m. Photoluminescence (PL) measurements for QWs having Sb compositions up to x   =  10% demonstrate strong room temperature PL up to 3.4 m, as well as enhancement of the PL intensity with increasing wavelength. To quantify the trends in the measured PL we calculate the QW spontaneous emission (SE), using a theoretical model based on an eight-band Hamiltonian. The theoretical calculations, which are in good agreement with experiment, identify that the observed enhancement in PL intensity with increasing wavelength is associated with the impact of compressive strain on the QW valence band structure, which reduces the band edge density of states making more carriers available to undergo radiative recombination at fixed carrier density. Our results highlight the potential of type-I InAs1− x Sb x /Al y   In1− y   As metamorphic QWs to address several limitations associated with existing heterostructures operating in the mid-infrared, establishing these novel heterostructures as a suitable platform for the development of light-emitting diodes and diode lasers.